Evaluation of aortic stiffness by echocardiography in tympanosclerosis patients - Hamur, Hikmet; Alper Onk, Oruc; Coskun, Resit; Cosgun, Muharrem Said; Salcan, Ismail; Emir, Izzet (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2023)
BACKGROUND AND AIMS: Tympanosclerosis (TS) is a scarring process that may occur during otitis media. Aortic stiffness (AS) is a significant predictor for the development of heart diseases due to its close relationship with atherosclerosis. Similar pathophysiological processes based on inflammation may explain both TS and AS formation. This study aimed to determine echocardiographically whether aortic elasticity is impaired in TS-detected patients and to correlate blood inflammatory parameters with TS and aortic elasticity. METHODS: Ninety-eight participants diagnosed with chronic otitis media were enrolled in the study. TS-detected 42 participants were assigned to the study group, while 56 without TS constituted the control group. The two groups' demographic, clinical, echocardiographic, and laboratory characteristics were comparable. RESULTS: Demographic, clinical, and laboratory parameter differences were insignificant. Hs-CRP, neutrophil-to-lymphocyte ratio, and systemic immune-inflammation index were significantly higher in the study group than in the control group (P=0.018, P=0.003, P=0.019, respectively). The study group had significantly lower aortic strain (11.80 ± 4.84 vs. 16.30 ± 3.91; P<0.001) and distensibility (5.23 ± 2.68 vs. 7.24 ± 2.89; P=0.001) values than the control group. The AS index was significantly higher in the study group than in the control group (4.81 ± 2.41 vs. 3.12 ± 1.02; P<0.001). CONCLUSION: In TS-detected patients, AS parameters were found to be impaired. Aortic elasticity parameters measured by echocardiography, a non-invasive and easily accessible method, may signify early cardiovascular involvement in TS-developed patients.
Keywords: echokardiografie; echocardiography; Inflammation; inflammation; Elasticity; lidé; zánět; pružnost; tympanosclerosis; Vascular Stiffness; tuhost cévní stěny; aortic stiffness; Otitis Media; otitis media; Echocardiography; Humans